The Role of Islamic Religious Education Psychology in Indonesian Education Management - Mulyono, Puput; Purnomo, Singgih (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
Islamic Religious Education (PAI) plays an important role in shaping students' character in Indonesia through an in-depth psychological approach. This study aims to identify PAI's contribution in strengthening moral and spiritual values, shaping religious identity, increasing tolerance between religious communities, and supporting students' academic achievement. This study uses a mixture of quantitative and qualitative methods. Quantitative data was collected through questionnaires on 20 students from various levels of education in Surakarta, while qualitative data was obtained through in-depth interviews with 15 PAI teachers in Muntilan. The results showed that students were delighted with PAI subjects and recorded good academic grades. Interviews revealed that teachers play a significant role in guiding students to understand and apply Islamic values daily. In addition, PAI has been proven to contribute to fostering tolerance, empathy, and harmony in a multicultural environment. The conclusion of this study emphasizes that PAI not only functions as a medium for the delivery of religious teachings but also as a strategic means in shaping the personality of religious, ethical students who can interact harmoniously in a plural society. Therefore, strengthening the quality of PAI learning is the key to national education management.